Habitus and performativity in teaching practice in the state school network of Piauí: implications of the ENEM policy (Práxis Educativa, 2024)
This article aims to analyze the implications of the National High School Examination (known by the acronym ENEM) policy for teaching practice. The question is: Has teaching practice in High School in Piauí, Brazil, been marked by performativity as part of the teaching professional habitus? In what way? In order to answer this question, the article is based on Bourdieu’s theoretical framework and his praxeological method. Semi-structured interviews were carried out with teachers from two schools in Piauí, which were subjected to Maingueneau’s discourse analysis. The results show that teaching practice has been structured by results targets, training and performative practices. This performative practice is incorporated by teachers because it is a strong element of the professional habitus, embodied in the meritocratic tradition as a symbolic discourse of social justice. Teachers adhere to performativity to the extent that their professional habitus is predisposed to incorporate it, in the dialectical relationship between subjectivity and their position in the social field.Keywords: Habitus. Performativity. National High School Examination.